2021
DOI: 10.1093/jpids/piaa173
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-Associated Adverse Events in Hospitalized Children

Abstract: Background Antibiotic-associated adverse events (AEs) in hospitalized children have not been comprehensively characterized. Methods We conducted a retrospective observational study of children hospitalized at The Johns Hopkins Hospital receiving ≥24 hours of systemic antibiotics. Consensus regarding antibiotic-associated AE definitions was established by 5 infectious diseases specialists prior to data collection. Two physicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“… 1 In future clinical decision-support tool iterations, we plan to evaluate other patient-level outcomes, such as adverse outcomes from antibiotic use, central line complications, length of stay, mortality, and readmission rates. We recognize that one-fifth of pediatric patients have adverse outcomes from antibiotic administration, 24 such as acute kidney injury or Clostridium difficile infections, and hypothesize that any reduction in culture ordering practice and subsequent antibiotic administration will improve patient care. With the integration of neonatal sepsis, fever and neutropenia, and meningitis into our future clinical decision-support tool, we also hypothesize earlier identification and treatment of these conditions with improved length of stay and functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 1 In future clinical decision-support tool iterations, we plan to evaluate other patient-level outcomes, such as adverse outcomes from antibiotic use, central line complications, length of stay, mortality, and readmission rates. We recognize that one-fifth of pediatric patients have adverse outcomes from antibiotic administration, 24 such as acute kidney injury or Clostridium difficile infections, and hypothesize that any reduction in culture ordering practice and subsequent antibiotic administration will improve patient care. With the integration of neonatal sepsis, fever and neutropenia, and meningitis into our future clinical decision-support tool, we also hypothesize earlier identification and treatment of these conditions with improved length of stay and functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the published literature regarding the consequences of antibiotic overuse and misuse is in the adult population. However, Same et al [21] found that among hospitalized children receiving at least 24 h of systemic antibiotic therapy, 21% of antibiotic courses were complicated by at least one adverse events. Furthermore, each additional day of antibiotic therapy in a hospitalized child was associated with a 7% increased odds of developing an adverse event.…”
Section: Introductionmentioning
confidence: 99%
“…This would reduce the number of surgical patients exposed to broad-spectrum antimicrobial therapy and contribute to antibiotic stewardship. Early de-escalation of postoperative antimicrobial therapy could also reduce the risk of antibiotic-associated adverse events ( 21 , 49 , 50 ) and the health care costs associated with administration of antibiotics ( 51 ).…”
Section: Discussionmentioning
confidence: 99%